2020
DOI: 10.2217/pme-2019-0064
|View full text |Cite
|
Sign up to set email alerts
|

‘It’s Much More Grey than Black and White’: Clinical Geneticists’ Views on the Oversight of Consumer Genomics in Europe

Abstract: Aim: Direct-to-consumer (DTC) genetic tests (GT) have created controversy regarding their risks and benefits. In view of recent regulatory developments, this article aims to explore the attitudes of European clinical geneticists toward the oversight of DTC GT. Materials & methods: Fifteen semi-structured interviews were performed with clinical geneticists based in ten European countries. The transcripts were thematically analysized in an iterative process. Results & conclusion: Respondents strongly sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…1 . There were two instances where two reports related to the same study (two newly identified records [ 22 , 23 ], and two identified by Goldsmith et al [ 7 ]. Therefore, this review identified a total of 25 studies that address the knowledge and views of HCPs on DTC-GT for further evaluation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1 . There were two instances where two reports related to the same study (two newly identified records [ 22 , 23 ], and two identified by Goldsmith et al [ 7 ]. Therefore, this review identified a total of 25 studies that address the knowledge and views of HCPs on DTC-GT for further evaluation.…”
Section: Resultsmentioning
confidence: 99%
“…Of these, fourteen studies were conducted in North America, either in the USA, Canada, or both [ 21 , 24 36 ]. Two studies were conducted in Europe and involved HCPs from several European countries [ 2 , 22 , 23 ]. One study was conducted in New Zealand [ 37 ], and one in Thailand, the only one conducted in a low-to-middle income country [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This makes it difficult to ensure that results are analyzed consistently by different testing laboratories, and this may raise questions about reliability of results. It is also difficult to determine what legislation or regulation will be applied to how DNA can, or has been, stored, shared and used; this may depend on the country in which the company and laboratory are based-as that could be in different locations (Kalokairinou et al, 2020;Savard, 2013). • Privacy: Data generated from online DNA testing may be shared or sold to other research groups or companies.…”
Section: The Hgsa's Position On Online Dna Testingmentioning
confidence: 99%